Analysis of the Kipas Counseling Model in Student Character Development: A Literature Review - Rochiyatin Rifai; Budi Purwoko; Bakhrudin All Habsy (CV. Publikasi Indonesia, 2026)
The ineffectiveness of Western counseling theory in the sociocultural context of Indonesia underscores the need for a model that is relevant and rooted in local values. This study aims to analyze in depth the KIPAS (Intensive, Progressive, Adaptive, and Structured Counseling) model as a holistic framework for student character development, with a special focus on the integration of the Catur Murti philosophy from Raden Mas Panji Sosrokartono. Using the Systematic Literature Review (SLR) method, this study surveyed the scientific literature from various databases covering the period 2009–2024. The results indicate that KIPAS has a solid philosophical foundation through the decolonization of Western epistemology and the positioning of local wisdom as the core of its practice. This model inherently prevents cultural encapsulation by redefining the counselor’s role from an “expert” to a cultural facilitator who understands problems as “interactional problem situations.” The primary mechanism of character development occurs through the internalization of the concept of Catur Murti (alignment of Creation, Taste, Speech, and Work), which enables character transformation from within, producing individuals who are honest (bares), confident (steady), and courageous (wani). The implications of these findings emphasize the need to transform the competencies of school counselors and to open a broader empirical agenda for follow-up research to test the effectiveness of the model across diverse cultural contexts.